2021
DOI: 10.1159/000512022
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Large Aplasia Cutis Congenita with Underlying Skull Defect: Effective Surgical Treatment with Integra® Dermal Regeneration Template

Abstract: <b><i>Introduction:</i></b> Aplasia cutis congenita (ACC) is a rare congenital abnormality characterized by the absence of a portion of skin at birth which most commonly involves the scalp and can affect the galea, the pericranium, the bone, and the dura mater. It can be an isolated condition or associated with other disorders. <b><i>Case Report:</i></b> We present a case of ACC with a large defect of the scalp and the underlying bone treated with the use of Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…In terms of the extent of involvement, to the best of the authors’ knowledge, our patient possibly has one of the largest extent in the reported literature, among surviving patients with ACC. Although there are numerous case reports of ACC, only a handful describe ‘extensive ACC’, including seven that involve the scalp,21 26–31 four that affect the trunk,32–35 and three that affect both the head and trunk . Among these, only the latter three36–38 are nearly as extensive as our patient, with only one of them having survived 38.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of the extent of involvement, to the best of the authors’ knowledge, our patient possibly has one of the largest extent in the reported literature, among surviving patients with ACC. Although there are numerous case reports of ACC, only a handful describe ‘extensive ACC’, including seven that involve the scalp,21 26–31 four that affect the trunk,32–35 and three that affect both the head and trunk . Among these, only the latter three36–38 are nearly as extensive as our patient, with only one of them having survived 38.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the management of extensive ACC. Different management strategies have been proposed, including conservative31 47–50 and surgical approaches 12 15 20 21 24 51–53…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When complications develop related to the defect, surgery becomes the preferred choice of treatment. 6 However, consideration should be given to preemptive surgical intervention to avoid the risk of major complications.…”
mentioning
confidence: 99%